(untitled) (Confluenţe Bibliologice, 2024)
The article explores the profound connection between people and religious music, highlighting its significance in the activities of the Romanian Orthodox Patriarchate during the Commemorative Year of Hymnographers and Church Singers. Sacred music, rooted in folk art, represents a symbiosis between Eastern and Western cultures, characterized by modal melody, harmony, modal polyphony, and captivating heterophony. Christian Orthodox music is perceived as a means through which believers draw closer to God, influencing their emotions and thoughts. The article addresses and proposes initiatives for revitalizing church musical traditions, including the establishment of a Faculty/Academy of Religious Music and the creation of a Church Singers’ Association. The importance of developing a Dictionary of Religious Music and a National Catalogue of Church Music Publications is emphasized, as well as the need for training courses and the promotion of events dedicated to religious music singers. The article also highlights the role of church singers in establishing parish libraries, church museums, and Sunday schools, emphasizing their importance in the pastoral, missionary, and social activities of the community.